Effect of argon flow rate and direct current bias on the growth of boron nitride coating in low-temperature plasma - Kallol Chakrabarty; Paul A. Baker; Vineeth M. Vijayan; Shane A. Catledge (AIP Advances, 2022)
A microwave plasma chemical vapor deposition system was used to synthesize cubic boron nitride (cBN) coatings on diamond seeded silicon substrates using direct current (DC) bias. Effects of the argon (Ar) flow rate and bias voltage on the growth of the cBN coatings were investigated. Hydrogen (H2), argon (Ar), a mixture of diborane in H2 (95% H2, 5% B2H6), and N2 were used in the feed gas. A DC bias system was used for external biasing of the sample, which facilitates the goal of achieving sp3 bonded cBN. Fourier Transform Infrared Spectroscopy (FTIR) and X-ray Photoelectron Spectroscopy (XPS) revealed the existence of sp3-bonded BN in the produced samples. With increasing Ar flow, the cBN content in the coating increases and reaches a maximum at the maximum Ar flow of 400 SCCM used in this study. High-resolution XPS scans for B1s and N1s indicate that the deposited coating contains more than 70% cBN. This study demonstrates that energetic argon ions generated in a microwave-induced plasma significantly increase cBN content in the coating.